Modern quasi-religious beliefs: on the border between sacred and secular - Yuvsechko, Yaroslav (Uniwersyteckie Czasopismo Socjologiczne, 2019)
The paper deals with actual problem of current stage of religious sphere’s development – the emergence and vigorous activity of movements and organizations that can be characterized as quasi-religious. We research the characteristics of quasi-religions as the separate phenomena that operate mainly in the form of secular organizations and that try to transform the identity of its members in their desired direction. It is emphasized that the concepts of quasi-religious and pseudo-religious beliefs are not identical and require of separate religious studies research. But it can be considered that common to both phenomena is only their arising at the boundaries between sacred and secular. The paper presents a review of quasi-religious concepts – from Tillich to Greil, as well as a description of quasi-religious practices and quasi-religious movements.